Isolasi dan Identifikasi Molekuler Kapang Penghasil Enzim Selulase dari Serasah Mangrove (Avicennia marina) di Daerah Mangkang Wetan Semarang - Hadistiyani Yusuf Hadistiyani; Wijanarka Wijanarka; Yustian Rovi Alfiansah (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2026)
Cellulase (EC 3.2.1.4) is an enzyme capable of degrading cellulose into glucose, cellobiose, and cellooligosaccharides. Cellulase enzymes can be produced by cellulolytic fungi originating from various environments, including the Avicennia marina mangrove ecosystem. However, most previous studies have primarily focused on the isolation and screening of cellulolytic fungi without systematically evaluating the influence of carbon sources on cellulase production and activity. Furthermore, research integrating enzyme activity assays with molecular identification of fungal isolates from mangrove litter remains limited. Therefore, this study aims to isolate cellulolytic fungi from mangrove litter capable of producing cellulase enzymes, test the influence of various carbon sources on enzyme activity, and identify fungal isolates using the Internal Transcribed Spacer (ITS) housekeeping gene. We used the spread plate technique to isolate cultivable fungi. The cellulolytic activity of the fungal isolates was tested qualitatively using Congo red staining and analyzed quantitatively using the 3,5-dinitrosalicylate (DNS) method with various carbon sources, such as 1 percent Carboxymethyl Cellulose (CMC), 1 percent cellobiose, Potato Dextrose Broth (PDB), and a combination of 5 percent CMC and 5 percent cellobiose. Enzyme activity assays were performed using a spectrophotometer at a wavelength of 580 nm. This study obtained 10 purified and cultivable fungal isolates from three samples collected from two sampling sites. Screening for cellulolytic fungi identified two isolates capable of forming clear zones around their colonies: isolates C3.3 and A3.3. Quantitative cellulase activity assays indicated that the optimal carbon source for cellulase production was a combination of 5 percent CMC and 5 percent cellobiose for isolate A3.3, with peak activity occurring on day 3 at 46,736.19 U/mL and a pH of 6.11. Molecular identification results showed that isolate C3.3 had 100 percent similarity to Aspergillus aculeatus, while isolate A3.3 had 99 percent similarity to Penicillium javanicum.